2010
DOI: 10.1002/jcp.22138
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative potential of resveratrol on proinflammatory cytokines, hyperglycemia mediated oxidative stress, and pancreatic β‐cell dysfunction in streptozotocin‐nicotinamide‐induced diabetic rats

Abstract: Chronic exposure of pancreatic beta-cells to supraphysiologic glucose causes adverse beta-cell dysfunction. Thus, the present study was aimed to investigate the hypothesis that oral administration of resveratrol attenuates hyperglycemia, proinflammatory cytokines and antioxidant competence and protects beta-cell ultrastructure in streptozotocin-nicotinamide-induced diabetic rats. Oral administration of resveratrol (5 mg/kg body weight) to diabetic rats for 30 days showed a significant decline in the levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
3
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(137 citation statements)
references
References 81 publications
6
125
3
3
Order By: Relevance
“…RV significantly reduced the elevated levels of TBARS and activities of catalase and glutathione-S transferase in the hepatic tissue compared to the methotrexate-treated group. RV (5 mg/kg bw for 30 days) found a reduction of the levels of blood glucose, glycosylated hemoglobin, TNF-alpha, interleukin-1-beta, interleukin-6, NF-kappaB p65 unit and NO with increase in plasma insulin in diabetic rats (29). Bi et al (30) found that RV treatment significantly inhibited the release of TNF-alpha and nitrite oxide induced by lipopolysaccharide (LPS) in rat cortical microglia and a mouse microglial cell line N9 in vitro.…”
Section: Discussionmentioning
confidence: 88%
“…RV significantly reduced the elevated levels of TBARS and activities of catalase and glutathione-S transferase in the hepatic tissue compared to the methotrexate-treated group. RV (5 mg/kg bw for 30 days) found a reduction of the levels of blood glucose, glycosylated hemoglobin, TNF-alpha, interleukin-1-beta, interleukin-6, NF-kappaB p65 unit and NO with increase in plasma insulin in diabetic rats (29). Bi et al (30) found that RV treatment significantly inhibited the release of TNF-alpha and nitrite oxide induced by lipopolysaccharide (LPS) in rat cortical microglia and a mouse microglial cell line N9 in vitro.…”
Section: Discussionmentioning
confidence: 88%
“…Along with the generation of ROS, relatively longterm exposure of MIN6 cells to insulin did appear to increase significantly the expressions of the antioxidant enzymes Cat and Gpx, as occurs with some other inducers of cellular stress (Tiedge et al 1997, Laybutt et al 2002, Palsamy & Subramanian 2010, Chetboun et al 2012, Bhakkiyalakshmi et al 2014, Tersey et al 2014, Vasu et al 2014. In contrast, the expressions of Sod1 and Sod2 were only slightly and not significantly increased by 24 and 48 h insulin exposure.…”
Section: :3mentioning
confidence: 79%
“…Moreover, GSH, a co-substrate for glutathione peroxidase activity, is another major intra-and extracellular antioxidant molecule and acts as a direct free radical scavenger by conversion to GSSG [13]. GSSG to GSH ratio is a good marker for estimation of redox status [12,22].…”
Section: Diabetic Heart and Oxidative Stressmentioning
confidence: 99%